Neurochemical studies into the mode of action of anticonvulsant drugs - Elhwuegi, Abdullah Salem (1981)
Single doses of phenobarbitone decreased the turnover rate of dopamine (DA) and noradrenaline (NA) and increased the whole brain levels of 5- hydroxytryptamine (5-RT) and gamma-aminobutyric acid (GABA) . Habituation to phenobarbitone increased the levels of DA in striata and midbrain and decreased that of cerebral hemispheres, leaving the total amount unchanged. Habituation resisted the depletion otherwise caused by alpha-methyl-p-tyrosine (alpha-m.p.t.) in the striata for DA and in the cerebral hemispheres for both DA and NA. Withdrawal of phenobarbitone decreased the levels of DA in the striata and both catecholamines in the cerebral hemispheres. Withdrawal increased the depletion of DA in the striata and cerebral hemispheres and that of NA in the cerebral hemispheres and midbrain caused by alpha-m.p.t. Withdrawal convulsions increased the levels of DA in the striata and decreased it in the cerebral hemispheres, leaving the total amount unchanged. NA was less in this group than it was in controls. Alpha-m.p.t. protected animals from convulsions. This group showed less DA in the striata and in the cerebral hemispheres and less NA in midbrain. Habituation to phenobarbitone increased the levels of 5-HT and 5-HIAA. Withdraiwal returned both levels to control values. While withdrawal convulsions decreased the levels of 5-HT, 5-HIAA levels were increased. Single doses of phenytoin increased the levels of DA in striata and NA in midbrain. It also increased the l levels of 5-HIAA in whole brain and decreased the depletion of 5-HIAA caused by p-chlorophenylalanine (p-c.p.a.) or pargyline. Long term administration of phenytoin increa sed the levels of dopamine in the striata and the midbrain and decreased that of the cerebral hemispheres. It also produced an increase in the level s of NA in the cerebral hemispheres. Similar effects were observed after alpha-m.p.t. Whole brain levels of 5-HT and 5- HIAA were increased after long term treatment with phentoin. Single doses of carbamazepine increased the levels of NA in the midbrain and decreased the depletion of 5-HIAA after p-c.p.a. and pargyline. The long term treatment with carbamazepine increased the total brain levels of 5- HT and 5-HIAA and those of DA in the striata and cerebral hemispheres and for NA in the cerebral hemispheres and midbrain. The same effect was seen after alpha-m.p.t. While NA and GABA levels were decreased in the primary focal area oneweek after cobalt implantation, 5-HIAA levels were increased. The same effect was seen for NA and 5-HIAA levels two weeks after cobalt implantation.